An analysis of global and local crosslinguistic influence in L1 Mandarin-L2 English learners of L3 Spanish (Uma análise da influência interlinguística global e local em aprendizes de Espanhol como L3, falantes de mandarim como L1 e inglês como L2) - Patience, Matt (Estudos da Língua(gem), 2019)
The present study investigated L3 phonetic crosslinguistic influence (CLI) in L1 Mandarin-L2 English-L3 Spanish speakers. The objective was to determine whether the L1 or the L2 was a stronger source of CLI in trilingual speakers of three typologically distinct languages, and to examine the extent to which L2 and L3 proficiency play a role. Two analyses were performed. In the global analysis, Spanish-speaking judges (N=22) listened to passages read by L1 Mandarin-L2 English-L3 Spanish speakers (N=17) with varying levels of L2 and L3 proficiency and attempted to identify the speakers’ native language. In the local analysis, the L3 production of the Spanish trill was examined, with the goal of determining whether the L1 or L2 was a more frequent source of transfer. The two analyses revealed that both the L1 and L2 were possible sources of transfer, although the L1 was a stronger source overall. L2 and L3 oral proficiency were not significant factors, revealing that other factors may be better predictors of the source of transfer. These findings are discussed in reference to their compatibility with the Typological Primacy Model and the L2 Status Factor Model. O presente estudo investigou a influência fonética interlinguística (CLI) em falantes de mandarim como L1, inglês como L2 e espanhol como L3. O objetivo foi determinar se a L1 ou a L2 era uma fonte mais forte de CLI em falantes trilíngues de três línguas tipologicamente distintas, e examinar até que ponto a proficiência de L2 e L3 desempenham um papel. Duas análises foram realizadas. Na análise geral, juízes hispânicos (N = 22) escutaram passagens lidas por falantes de mandarim como L1, de inglês como L2 e de espanhol como L3 (N = 17) com diferentes níveis de proficiência da L2 e da L3, e tentaram identificar o idioma nativo dos indivíduos. Na análise local, a produção da vibrante múltipla alveolar da L3 foi examinada, a fim de determinar se a L1 ou a L2 foi uma fonte mais frequente de transferência. As duas análises revelaram que tanto a L1 quanto a L2 foram possíveis fontes de transferência, embora a L1tenha sido uma fonte mais forte no geral. A proficiência oral de L2 e L3 não foi um fator significativo, revelando que outros fatores podem ser melhores preditores da fonte de transferência. Essas descobertas são discutidas em referência à sua compatibilidade com o Modelo de Primazia Tipológica e o Modelo do Status da L2 como fator.